Novel treatment of the deformation–induced topographic effect for interpretation of spatiotemporal gravity changes: Laguna del Maule (Chile) - Vajda, Peter; Zahorec, Pavol; Miller, Craig A.; Le Mével, Hélène; Papčo, Juraj; Camacho, Antonio G. (Journal of volcanology and geothermal research, 2021)
In volcano gravimetry, when analyzing residual spatiotemporal (time-lapse) gravity changes, the accurate deformation-induced topographic effect (DITE) should be used to account for the gravitational effect of surface deformation. Numerical realization of DITE requires the deformation field available in grid form. We compute the accurate DITE correction for gravity changes observed at the Laguna del Maule volcanic field in Chile over three nearly annual periods spanning 2013–2016 and compare it numerically with the previously used free-air effect (FAE) correction. We assess the impact of replacing the FAE by DITE on the model source parameters of analytic inversion solutions and apply a new inversion approach based on model exploration and growing source bodies. The new inversion results based on the DITE correction shift the position of the mass intrusion upwards by a few hundred meters and lower the total mass of the migrated fluids to roughly a half, compared to the inversion results based on the local-FAE correction. Our new Growth inversion results indicate that vertical dip-slip faults beneath the lake, as well as the Troncoso fault play active roles in hosting migrating liquid. We also show that for the study period, the DITE at Laguna del Maule can be accurately evaluated by the planar Bouguer approximation, which only requires the availability of elevation changes at gravity network benchmarks. We hypothesize that this finding may be generalized to all volcanic areas with flatter or less rugged terrain and may modify interpretations based on the commonly used FAE corrections. •accurate DITE correction to be used for computing 4D micro-gravity changes.•impact of not using DITE on inversion and interpretation illustrated by case study.•Bouguer approximation of DITE shown accurate in less rugged areas.•Growth inversion tool applied to sparse scattered inaccurate 4D micro-gravity data.